(untitled) (Scientific journal of the Fergana State University, 2023)
The article considers the problem of cognitive development of preschool children as a result of the action of a number of factors of an objective and subjective nature and the need for its early diagnosis and correlation as a condition for the effectiveness of learning and the success of personality development.